The mother's knowledge regarding worms in pre-school students in PAUD Salsabila, Yogyakarta - Anggraeni, Dwi; Wijaya, Liza (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: Most individuals tend to view helminthic disease as a very minor illness. Despite the fact that this illness might worsen children's health because of things like low body weight, anemia, problems with growth and development, and delayed cognitive development. Purpose: This study aims to determine the mother's knowledge regarding worms among pre-school students in PAUD Salsabila, Yogyakarta. Methods: This study used a descriptive design and was quantitative in nature. Mothers whose preschool-age children attend PAUD Salsabila in Yogyakarta comprise the study's population. Using the total sampling technique, 32 moms provided the sample for this investigation. Results: The results indicated that the majority of moms possess moderate information about worms. The characteristics of respondents in this study include the majority of mothers aged 26–35 years, which is as many as 17 people (53%). The majority of respondents had elementary school education, which was 12 people (37.5%) and the majority of respondents are housewives, 21 people (65.6%). Conclusion: The overall level of maternal knowledge regarding the prevention and control of intestinal parasites in this study was classified as moderate.